2004
DOI: 10.1002/cncr.20442
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of Csk homologous kinase (CHK) in normal brain and brain tumors

Abstract: Approximately 9% of deceased kidney donors are classified by the Centers for Disease Control as high infectious risk donors (HRDs), donors thought to be at increased risk for having HIV infection. While the use of HRDs expands the organ supply, there is a small risk of infectious transmission. All donors are tested for antibodies to a variety of viral infections including HIV, hepatitis C virus (HCV), and hepatitis B virus; however, infections acquired in the weeks to months before death may not be serological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 59 publications
0
21
0
1
Order By: Relevance
“…Nuclear localization of ectopic CHK has previously been observed in monkey kidney fibroblast COS-1 cells, and overexpression of CHK induced multinucleation, which in combination with other data, suggested a potential role of CHK in chromosome dynamics (Yamaguchi et al, 2001). Nuclear staining of endogenous CHK has also been reported in normal human brain tissues (Kim et al, 2004). It appears that nuclear CHK induces nuclear multilobulation in late S-phase and inhibition of proliferation (Nakayama and Yamaguchi, 2005).…”
Section: Chk Inhibits Src In Normal Colon Cellsmentioning
confidence: 88%
“…Nuclear localization of ectopic CHK has previously been observed in monkey kidney fibroblast COS-1 cells, and overexpression of CHK induced multinucleation, which in combination with other data, suggested a potential role of CHK in chromosome dynamics (Yamaguchi et al, 2001). Nuclear staining of endogenous CHK has also been reported in normal human brain tissues (Kim et al, 2004). It appears that nuclear CHK induces nuclear multilobulation in late S-phase and inhibition of proliferation (Nakayama and Yamaguchi, 2005).…”
Section: Chk Inhibits Src In Normal Colon Cellsmentioning
confidence: 88%
“…CHK is highly expressed in neural tissue, especially in neurons. It was shown that Csk and CHK exhibit opposite temporal expression in the CNS (12,13). Previously, we observed a different pattern of expression for CHK and Csk in brain malignancies (13).…”
Section: Introductionmentioning
confidence: 66%
“…It was shown that Csk and CHK exhibit opposite temporal expression in the CNS (12,13). Previously, we observed a different pattern of expression for CHK and Csk in brain malignancies (13). While Csk expression is not altered in brain malignancies, CHK expression is significantly downregulated in some brain tumor types (13).…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations